2019
DOI: 10.1155/2019/2603098
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Joint Replacement in a Thumb Interphalangeal Joint

Abstract: Arthrodesis of the interphalangeal (IP) joint of the thumb is widely acknowledged as the indicated treatment for trauma and osteoarthritis of this joint. Joint replacement was offered to a young patient as an alternative treatment after traumatic joint loss of the IP joint in her thumb. This allowed her to maintain motion of the joint as she did not wish to move forward with fusion. In the present case, a Humanitarian Use Device (HUD) was utilized in an off-label manner and placed into the interphalangeal join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Arthroplasty of the thumb IPJ is not common. Only one other case report exists using a synthetic joint made of polyethylene, cobalt chrome, and titanium, and achieved excellent functional results [6]. The advantage of using autologous material over synthetic is that the tissues are revascularized.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroplasty of the thumb IPJ is not common. Only one other case report exists using a synthetic joint made of polyethylene, cobalt chrome, and titanium, and achieved excellent functional results [6]. The advantage of using autologous material over synthetic is that the tissues are revascularized.…”
Section: Discussionmentioning
confidence: 99%
“…McKee et al [6] reported a 15-year-old trauma patient, who presented with an intra-articular fracture and adjacent laceration at the distal portion of the proximal phalanx of the thumb resulting in near complete loss of the interphalangeal joint after a table saw accident. is patient had a surface gliding implant arthroplasty and a tendon repair.…”
Section: Discussionmentioning
confidence: 99%
“…ere also is no proof that blocking the IP joint might speed up the development of arthritis in the MCP and CMC joints. Very few reports about IP joint arthroplasty have been described so far [5,6]. We offered this alternative technique to patients desiring to keep some motion of the IP joint, assuming that they would benefit from it, by reducing pain and improving dexterity in their activities and potentially avoiding an early onset of arthritis in the more proximal joints of the thumb.…”
Section: Introductionmentioning
confidence: 99%
“…Der Kunstgelenksersatz mit einem Silikonspacer am Endgelenk wurde in 2 Publikationen bzw. Case-reports beschrieben[21,22]. Die Anwendung von Oberflächen-Gleitprothesen wurde in zwei Serien mit 7 Patienten bzw 13.…”
unclassified